Peningkatan Angka Kebuntingan melalui Pemberian Hormone Eksogen CIDR-B dan Injeksi hCG pada Sapi Bali di Kecamatan Pemayung Kabupaten Batang Hari - Depison, Depison (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2009)
This  eksperiment  was  conducted  in  order  to  know  1) The  effect  of  hormone  CIDR-B  and  the injection of hCG on increased conception rates in post-IB Bali cattle in Sub District Pemayung Batang Hari. 2) Application and dissemination  technology of the use of exogenous hormone in improving the reproductive performance of Bali cattle, especially in villages in the subdistrict Pemayung Batang Hari. The method used to reveal the data was an experiment by using 90 Bali cattle in several villages in the District Pemayung. The treatments used were R1 (control) without treatment, R2, Hormones CIDR-B, R3 hCG injection. The average value of non-return rate (NR) results of these activities was 68.89%. The use of CIDR-B was implanted day 7 to day 14 after IB and hCG day 7 post-IB in sequence to increase the number  of  animals  who  did  not  return  estrus  compared  with  no  hormonal  treatment  by  20%  and 16.66%. The average parent who declared pregnant Bali cattle after pregnancy examination (PKB) at 2 months  of  gestation  was  60%.  Based  on  the  results  and  the  discussion  can  be  concluded  that  the provision of exogenous hormones CIDR-B and hCG can increase gestation Bali cattle in terms of NR and CR and the best was the use of hormone CIDR-B.